Assessment of the Perception of People Living With HIV Regarding the Quality of Outpatient Care at a Reference Facility in the Federal District, Brazil - Silva, Andressa Wanneska Martins da; Meiners, Micheline Marie Milward de Azevedo; Gallo, Luciana Guerra; Oliveira, Ana Flávia de Morais; Aridja, Ursila Manga; Noronha, Elza Ferreira (Frontiers in Pharmacology, 2021)
The effectiveness of antiretroviral treatment has transformed HIV infection into a chronic transmissible condition, requiring health systems to adapt in order to care for people living with HIV. The Chronic Care Model (CCM) is the gold standard for this type of care in many countries. Among its tools, the Patient Assessment of Chronic Illness Care (PACIC) questionnaire gives the patient’s perspective of the care provided. The aim of the present study was to adapt and apply, for the first time, the questionnaire to people living with HIV to determine their perception of the quality of care provided at a reference hospital in the Federal District of Brazil. This is a case study conducted in 2019 at a teaching hospital, with a convenience sample of 30 individuals treated for at least one year at the facility. The median PACIC score (3.5 with a range of 1.0-5.0) seems to suggest that the users perceive the outpatient care provided by the hospital as being basic. The “delivery system design/ decision support” component was deemed the best (5.0, with a range of 1.0-5.0) and “follow-up/coordination” the worst (1.0, with a range of 1.0 - 5.0). The results suggest the need to improve the organization of care and make adequate use of community resources, in line with the CCM. The questionnaire makes it possible to determine the strengths and weaknesses of the care provided to people living with HIV and can be used as a planning and monitoring tool to improve management of the condition, with the contribution of the patient, in particular, thereby strengthening self-care.